2009
DOI: 10.1007/s00234-008-0487-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and additional value of diffusion-weighted imaging for discrimination of malignant cervical lymph nodes in head and neck squamous cell carcinoma

Abstract: Introduction The aim was to determine the diagnostic accuracy and additional value of diffusion-weighted imaging for detection of malignant lymph nodes in head and neck squamous cell carcinoma.Methods Two hundred nineteen lymph nodes, predominantly smaller than 10 mm (95.4%), in 16 consecutive patients were evaluated at 1.5 T. Lymph nodes were evaluated for maximum short axial diameter, morphological criteria, and apparent diffusion coefficient (ADC) values (b=0 and b=1,000 s/mm 2 ). Sensitivity, specificity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 26 publications
6
102
2
2
Order By: Relevance
“…Integrated PET/MR opens new perspectives in biomedical research and clinical multimodality imaging [3][4][5][6]. In addition to better soft tissue contrast and lack of ionizing radiation exposure, MRI offers a wide range of advanced imaging techniques [7,8], such as apparent diffusion coefficient maps for quantification of cellular density [9], arterial spin labelling for measurement of blood flow [10], dynamic contrast enhancement to assess the characteristics of tumour vasculature, including perfusion, blood vessel permeability, blood volume and extravascular extracellular volume fraction [11], and quantification of tissue metabolite concentrations by calibrated 1 H-MR spectroscopy [12,13] or based on hyperpolarized 13 C [14]. Hence, multiparametric PET/MR has the potential to become a powerful tool for accurate primary diagnosis and early evaluation of therapy response.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated PET/MR opens new perspectives in biomedical research and clinical multimodality imaging [3][4][5][6]. In addition to better soft tissue contrast and lack of ionizing radiation exposure, MRI offers a wide range of advanced imaging techniques [7,8], such as apparent diffusion coefficient maps for quantification of cellular density [9], arterial spin labelling for measurement of blood flow [10], dynamic contrast enhancement to assess the characteristics of tumour vasculature, including perfusion, blood vessel permeability, blood volume and extravascular extracellular volume fraction [11], and quantification of tissue metabolite concentrations by calibrated 1 H-MR spectroscopy [12,13] or based on hyperpolarized 13 C [14]. Hence, multiparametric PET/MR has the potential to become a powerful tool for accurate primary diagnosis and early evaluation of therapy response.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6]9,19 Although lower ADC values were reported at 3T than at 1.5T in the brain 20 and in abdominal organs, 21 there was no significant statistical difference for different field strength in neck imaging. 7 The water diffusivity should not depend on the magnetic field strength, because the molecular motion is purely a thermal phenomenon, not a nuclear MR characteristic.…”
Section: Discussionmentioning
confidence: 92%
“…DWEPI provides a quantitative measurement of the ADC of water protons in tissue. According to recent reports, an ADC value that is significantly lower in the metastatic LNs than that in the benign LNs can be used to differentiate malignant LNs from benign LNs [3][4][5][6] and can be a marker for prediction and early detection of chemoradiation therapy response. 7,8 DWEPI also can be used for the early detection of recurrence.…”
mentioning
confidence: 99%
“…For lymph node staging ADC values have found to be the strongest independent predictor for the presence of nodal metastases [49] and significantly improve the detection of small metastatic lymph nodes (4 -9 mm), which remain false-negative based on pure size and morphology criteria [50]. For the evaluation of treatment response it has been shown that two-week intra-treatment ADCs are predictors of outcome, as a lower increase in the percentage change of the mean ADC, higher skewness, and higher kurtosis are significantly more likely to show local failure than local control [51].…”
Section: Diffusion-weighted Imaging (Epi-dwi Non-epi-dwi Resolve)mentioning
confidence: 99%
“…The advantages of suppressing the signal from fat is to suppress artifacts due to high fat signals, to improve T2 contrast between fatty and non-fatty tissue, to enable detection of enhancing tumors hidden in fatty tissue, and the proof of adipose tissue, such as in lipoma, or cholesterol granuloma. Reading T1w and T2w basic sequences and T2w fat sat images is important because the very high STIR/TIRM ▶ Table 1 (Continuation) MRI sequences main pathologies/field of application diagnostic clues paraganglioma high peak enhancement, SER, and short TME on DCE [37] schwannoma low peak enhancement and SER with a longer TME on DCE [37] diffusionweighted imaging primary tumors low ADC values (lymphoma, followed by carcinoma, benign tumor and cystic lesions) [47] lymph node staging low ADC values [49] residual cancer after chemoradiation therapy lower increase in the percentage change of the mean ADC or decrease in ADC during treatment [51,52] cholesteatoma high signal on DWI [60] Granulation tissue, fibrous tissue, cholesterol granuloma or serous fluid…”
Section: Introductionmentioning
confidence: 99%